Japanese diasporas : unsung pasts, conflicting presents, and uncertain futures - Adachi, Nobuko (Routledge studies in Asia's transformations., 2006)
An examination of the relationship of overseas Japanese and their descendents (Nikkei) with their home and host nations, focusing on their political, social and economic struggles. The authors suggest some of the ways in which diasporas are transforming global society today.--